Coupling of piezoelectric, semiconducting and photoexcitation properties in NaNbO3 nanostructures for controlling electrical transport: Realizing an efficient piezo-photoanode and piezo-photocatalyst. (August 2017) - Singh, Simrjit; Khare, Neeraj
Abstract: Piezophototronic effect in semiconductors such as ZnO and BaTiO3 has been studied earlier but chemical instability and insulating nature of these respective materials make them unsuitable for photoelectrochemical (PEC) and photocatalytic applications. Herein, we demonstrate an efficient coupling between piezoelectric, semiconducting and photoexcitation properties in chemically stable NaNbO3 semiconductor with an aim to enhance the efficiency of PEC water splitting and photocatalytic activities. We show that an alternating built-in potential can be generated in NaNbO3 nanostructures under periodic mechanical strain resulting in improved charge separation of the photogenerated charge carriers. NaNbO3 particulate suspension shows a large (~115%) enhancement in the photodegradation rate of organic dyes in industrial waste water which is much higher than the earlier reported piezophotocatalytic activity in ZnO. For PEC water splitting activity, NaNbO3 nanostructure films deposited onto flexible ITO coated polyethylene terephthalate (ITO/PET) substrates were polarized by applying an external electric field. Enhancement in the photocurrent density from 0.78 mA/cm 2 to 1.02 mA/cm 2 and ~8% improvement in the incident photon to current conversion efficiency have been noted under the piezoassistance. Our present work demonstrates an efficient coupling between mechanical, optical and electrical properties in NaNbO3 thus, it can be used as a potential alternative material for piezophototronic applications. Graphical abstract: Highlights: Demonstrated piezo-phototronic effect induced enhancement in the photocatalytic and photoelectrochemical properties of chemically stable NaNbO3 nanostructures. NaNbO3 nanostructures show ~115% enhancement in the photocatalytic activity for the degradation of methylene blue dye. NaNbO3 nanostructure films show ~8% enhancement in the incident photon to current efficiency. An alternative material for piezophototronic applications.